Educação em ciências e a infância: por uma visão as crianças - Silva, Tássia Cabral da (2019)
Based on the assumption of the child as a social actor of law, defended by the Sociology of Childhood, this field of study was the theoretical-methodological basis for the investigation. The main objective of this study was to understand the conceptions about child participation in the construction of knowledge in Science Education. Therefore, using a phenomenological posture, with the intention of interpreting actions and reflecting their intentionality, a qualitative investigation was carried out, having as participants a group of 17 pre-school children and their teacher. We use for data generation: research tools, participant observation, field diary, photographs and conversations. In the course of the investigation it was found that recognizing the child as a social actor is important for the construction of a new view, where they are seen as competent beings who actively participate in their social environment. We also consider that early science education corroborates the construction and formation of an ethical and responsible attitude of the child with the other and with the world. The study shows that the participation of children in pedagogical practices is an essential instrument to develop an educational environment based on respect and appreciation of the voice of the child. Therefore, it requires the commitment, involvement and especially the practice of listening and observing the actions and manner of the children to express their point of view